2005
DOI: 10.1002/jcd.20091
|View full text |Cite
|
Sign up to set email alerts
|

Types of superregular matrices and the number ofn‐arcs and completen‐arcs in PG (r, q)

Abstract: Based on the classification of superregular matrices, the numbers of non-equivalent n-arcs and complete n-arcs in PG(r, q) are determined (i) for 4 q 19, 2 r q À 2 and arbitrary n, (ii) for 23 q 32, r ¼ 2 and n ! q À 8. The equivalence classes over both PGL (k, q) and PÀ ÀL(k, q) are considered throughout the examinations and computations. For the classification, an n-arc is represented by the systematic generator matrix of the corresponding MDS code, without the identity matrix part of it. A rectangular matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…In Table 2 we give the updated list of the known sizes of complete arcs in PG (2, q). Note also that in [59] it is shown that m 2 (2, 31) = 22, m 2 (2, 32) = 24.…”
Section: Construction Cmentioning
confidence: 99%
“…In Table 2 we give the updated list of the known sizes of complete arcs in PG (2, q). Note also that in [59] it is shown that m 2 (2, 31) = 22, m 2 (2, 32) = 24.…”
Section: Construction Cmentioning
confidence: 99%
“…In particular, a complete arc in a plane PG (2, q), the points of which are treated as 3-dimensional q-ary columns, defines a parity check matrix of a q-ary linear code with codimension 3, Hamming distance 4, and covering radius 2. Arcs can be interpreted as linear maximum distance separable (MDS) codes [74,Sec.7], [76] and they are related to optimal coverings arrays [43], superregular matrices [49], and quantum codes [19].…”
Section: Introduction the Main Resultsmentioning
confidence: 99%
“…Superregular matrices with entries in a finite field can be obtained from Cauchy matrices or Vandermonde matrices (see, for example, [15,16,19,20]). …”
Section: Resultsmentioning
confidence: 99%